2007
DOI: 10.1002/eji.200737418
|View full text |Cite
|
Sign up to set email alerts
|

Back to the future –defining NK cells and T cells

Abstract: In this issue of the European Journal of Immunology (EJI), Stewart et al. report about a population of cd-T cells expressing an extensive repertoire of NK cell receptors, and the presence of non-rearranged germline TCRd transcripts in conventional NK cells. These findings and other recent studies highlight the similarities of NK cells and T cells and the problems in discriminating between these two lineages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…null T cells have suggested that they are related to NK cells and represent a population of NK-like T cells [29]. In support of this hypothesis, we found that CD4 +…”
Section: Cd28supporting
confidence: 87%
“…null T cells have suggested that they are related to NK cells and represent a population of NK-like T cells [29]. In support of this hypothesis, we found that CD4 +…”
Section: Cd28supporting
confidence: 87%
“…Unlike naive T cells, effector memory CD8 T cells commonly express receptors originally found on natural killer (NK) cells, and therefore are often referred to as NK receptors. [5][6][7][8][9] Among these are members of the leukocyte receptor complex (LRC)-encoded killer cell immunoglobulin like receptors (KIR) as well as members of the natural killer gene complex (NKC)-encoded C-type lectin-like receptors (CTLR). [7][8][9] Examples of NKC-encoded CTLR expressed on T cells are mouse Ly49 family MHC class I receptors and killer lectin-like receptor (KLR) family members such as CD94/NKG2A and KLRG1.…”
Section: Introductionmentioning
confidence: 99%
“…Such immunophenotypic sharing by NK and T cells blurs the distinction between these cell types. 3,4 Analysis of T-cell receptor gene (TCR) rearrangements is the gold standard to distinguish T from NK cells. The productive rearrangement of the TCR gene in mature T cells distinguishes the two cell types unambiguously.…”
mentioning
confidence: 99%
“…The productive rearrangement of the TCR gene in mature T cells distinguishes the two cell types unambiguously. 4 TCR gene rearrangement analysis using Southern blot hybridization or nested polymerase chain reaction (PCR) analyses disclosed variable T-cell clonality in ENKTLs ranging from 0 to 27%. 5,6 The BIOMED-2 Concerted Action protocol using multiplex PCR primers has now replaced conventional PCR in assaying gene rearrangements and has higher sensitivity than conventional PCR analyses that use fewer primer sets.…”
mentioning
confidence: 99%